Biography, romance and chivalry : Barbour's The Bruce and Chandos Herald's La vie du Prince Noir - Foran, Susan (Trinity College (Dublin, Ireland). Department of History, 2007)
The aim of this thesis is to establish the form and function of two late fourteenth- century biographies of royal subjects in Britain: John Barbour’s The Bruce, which was written circa 1375, and Chandos Herald’s La vie du Prince Noir, arguably composed circa 1385. The Bruce is a biography of Robert Bruce (Robert I of Scotland, 1306-1329) and Sir James Douglas, his trusted companion, written for the court of Robert II (1371-1390), Robert I’s grandson and the first Stewart king of Scotland. La vie du Prince Noir is a record of the deeds of the life of the so-called Black Prince, Edward of Woodstock, Prince of Wales, duke of Aquitaine and heir-apparent (1330-1376) to King Edward III. It is argued that both these biographies are royal commissions and reflect a reconciliation of a contemporary chivalric ethos promoting a system of individual values with a collective enterprise advocated by the courts for which they were composed
Keywords: Medieval History, Ph.D.; Ph.D. Trinity College Dublin